2013
DOI: 10.1002/oby.20336
|View full text |Cite
|
Sign up to set email alerts
|

NFκB as a potent regulator of inflammation in human adipose tissue, influenced by depot, adiposity, T2DM status, and TNFα

Abstract: Objective: Central obesity and sub-clinical inflammation increase metabolic risk, this study examined the intracellular inflammatory pathways in adipose tissue (AT) that contribute to this risk. Design and Methods: This study therefore addressed the influence of NFjB and JNK activation in human abdominal subcutaneous (AbdSc) and omental (Om) AT, the effect of adiposity, T2DM status and the role of TNFa in vitro, using molecular biology techniques. Results: Our data showed NFjB activity is increased in Om AT ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…In particular visceral AT, including omental adipose tissue (OAT), is associated with adverse metabolic consequences of obesity . Besides expansion of (O)AT, obesity coincides with adipose tissue (AT)‐inflammation, characterized by hypertrophic adipocytes, increased influx of immune cells, and inflammasome activation . Subsequent disproportionate pro‐inflammatory adipokine secretion elicits a local immune response, propagated by communication between adipocytes and macrophages, generating a self‐sustaining reciprocal pro‐inflammatory loop .…”
Section: Introductionmentioning
confidence: 99%
“…In particular visceral AT, including omental adipose tissue (OAT), is associated with adverse metabolic consequences of obesity . Besides expansion of (O)AT, obesity coincides with adipose tissue (AT)‐inflammation, characterized by hypertrophic adipocytes, increased influx of immune cells, and inflammasome activation . Subsequent disproportionate pro‐inflammatory adipokine secretion elicits a local immune response, propagated by communication between adipocytes and macrophages, generating a self‐sustaining reciprocal pro‐inflammatory loop .…”
Section: Introductionmentioning
confidence: 99%
“…It is known that NF‐κB is important in the process of insulin resistance 38 and T2D 39. It has been shown that CARD9‐deficient cells are defective in zymosan‐induced NF‐κB activation 3.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of NF-jB and other transcription factors further induce the expression of various cytokines and chemokines and inflammatory responses. It is known that NF-jB is important in the process of insulin resistance [38] and T2D [39]. It has been shown that CARD9-deficient cells are defective in zymosan-induced NF-jB activation [3].…”
mentioning
confidence: 99%
“…The nonsignificant differences are attributed to the small size number of participants. Previous studies mentioned that several inflammatory biomarkers are increased in obesity and many authors believed that these proinflammatory markers played a role in the etiology of obesity [4,5,6]. C-reactive protein was strongly related to total and central abdominal obesity, blood pressure, and lipid levels, independent of genetic influences [7].…”
Section: Discussionmentioning
confidence: 99%